ANALISIS KETUNTASAN HASIL BELAJAR PENGETAHUAN PADA MATERI SISTEM ORGANISASI KEHIDUPAN DI SMP NEGERI 1 SIDOARJO PADA MASA PANDEMI - Mega Ayuna Rizki; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The research was to analyze the completion of junior high school students learning outcomes during online learning during the Covid-19 pandemic. This type of research is quantitative research with descriptive method. The subject of the study was 30 students of grade VII E smp negeri 1 Sidoarjo. Data collection techniques using research instruments in the form of knowledge sheets of Life Organization System Materials and questionnaires of student responses to online learning. The data collection process is done online through Google Forms. The results obtained indicate that the classical student learning outcomes are 76,67% in the complete category. Judging from the completion of individual knowledge learning outcomes, there were 23 students declared complete and 7 students declared incomplete. The results of the questionnaire on student responses to online learning at SMP Negeri 1 Sidoarjo were presented using percentage diagrams. The average percentage obtained is that 94.18% of students have the availability of tools or facilities used during online learning, 76,66% of students have an interest in online learning, 72.20% of students state that the materials submitted by teachers during online learning are relevant. In addition, 66.66% of students have obstacles during online learning, and 72.20% of students are satisfied with the results obtained during online learning. Based on the results of the research, it can be concluded that students have some obstacles experienced online learning such as feeling bored and lack of understanding of the materials taught. These barriers can be a factor that affects student learning outcomes. Therefore, an online learning evaluation process is needed to improve students learning outcomes during the Covid-19 pandemic.